The Main Directions of Formation and Development of Safety Culture in the Russian Federation - Lyskova, I. E. (Глобальная ядерная безопасность, 2022)
The article actualizes the political, legal, socio-economic and socio-cultural aspects of safety culture in the Russian Federation. The article offers a general analysis of the current regulatory framework that defines the conceptual foundations for the formation and development of a culture of life safety, a culture of economic security and environmental culture in the Russian Federation.